A Study on the Pattern of Drug Administration in Patients with Postoperative Hand Trauma Treated with Herbal Fumigation based on Data Mining Analysis - Li, Yingchun; Dong, Bo (Journal of Contemporary Medical Practice, 2024)
Objective: To analyze the dosing pattern of patients with postoperative hand trauma treated with traditional Chinese medicine topical fumigation based on the data mining method. Methods: Information retrieval of major domestic and foreign large databases such as know.com and pubmed was applied to the computer, and the retrieval time was limited to the period from the establishment of the database to Sep 1, 2022, to collect clinical literature related to Chinese medicine for the treatment of postoperative patients with hand trauma, and EXCEL 2018 software was applied to establish the database with the retrieval results, and frequency analysis, nature and flavor attribution analysis, and drug class analysis were performed. The spss statistics23.0 and SPSS statistics Modeler 18.0 software were applied to perform high-frequency drug clustering analysis and association rule analysis, respectively. Results: Among the traditional Chinese medicines for the treatment of postoperative hand trauma patients, the high-frequency Chinese medicines mainly included safflower, elongated tendon grass, transverse bone grass The results of the cluster analysis showed that six drug groups were available, with the most drugs for dispelling wind and dampness, activating blood circulation and relieving pain. The pair of Radix Rehmanniae and Radix Angelicae Sinensis had the highest support. Conclusion: The analysis of the pharmacological pattern of herbal fumigation treatment for postoperative hand trauma patients through data mining shows that the pathogenesis of postoperative hand trauma patients is qi stagnation, blood stasis and wind-damp paralysis. Their treatment should follow the therapeutic principles of dispelling wind and dampness, invigorating blood and removing blood stasis.